An examination on child protection as a basis for enhancing early childhood education of sexually abused children in Kinangop Sub-County, Kenya - Ndegwa, Mary Wambui; Edabu, Dr. Paul (IJRDO- Journal of Educational Research, 2016)
All children are entitled to a basic right to education as enshrined in Basic Education Act, 2012. However, realization of such rights has faced numerous challenges though little has been done to establish the influence of child sexual abuse. Thus, this study aimed to examine child protection as a basis for enhancing early childhood education of sexually abused children in Kinangop Sub-county. This study was guided by The Attachment Theory which was postulated by Bowlby (1990). The study adopted mixed methods approach and a descriptive survey. Target population comprised the 53 ECDE Center managers, 146 ECDE Teachers, 106 parents‟ representatives, five Children‟s officers and 1190 ECDE Children all totaling to 1500. The researcher sampled 20% of the targeted ECDE Centers, that is, ten ECDE Centers. Similarly, based on the same proportion, 20% of the target population, that is, 300 respondents were sampled. Stratified sampling was applied to create five strata based on the number of zones in Kinangop Sub-county. From each stratum, two ECDE Center managers and nine ECDE Teachers were selected using purposive sampling. The Children‟s Officers were also selected using purposive sampling. Six parents‟ representatives and 43 ECDE children were selected using simple random sampling. Qualitative data was analyzed based on research objectives while quantitative data was analyzed using ANOVA in Statistical Packages for Social Science (SPSS Version 21). The study established that applicability of child protection amongst sexually abused children has not been fully realized. The study thus recommends that stakeholders should be trained on different child protection measures so that they can be able to identify and prevent cases or potential instances of child sexual abuse (CSA).